2015
DOI: 10.1128/aac.01255-15
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin Resistance at the China-Myanmar Border and Association with Mutations in the K13 Propeller Gene

Abstract: cArtemisinin resistance in Plasmodium falciparum parasites in Southeast Asia is a major concern for malaria control. Its emergence at the China-Myanmar border, where there have been more than 3 decades of artemisinin use, has yet to be investigated. Here, we comprehensively evaluated the potential emergence of artemisinin resistance and antimalarial drug resistance status in P. falciparum using data and parasites from three previous efficacy studies in this region. These efficacy studies of dihydroartemisinin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
101
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(117 citation statements)
references
References 39 publications
16
101
0
Order By: Relevance
“…It is important to note that although parasite isolates from the two study sites showed widely different in vitro sensitivities to AS and DHA, these values do not correlate with clinical outcomes. Studies conducted along the China-Myanmar border area have shown overall excellent efficacies of ACTs (25)(26)(27), but slowed parasite clearance and 3-day parasite positivity after ACT treatment were also detected (28,29), indicating possible emergence of artemisinin resistance in this region. For the only known molecular marker of artemisinin resistance, pfk13, earlier data showed that the prevalent K13 mutation in the Shan State is P574L (30), which is correlated with artemisinin resistance (8), whereas the most prevalent K13 point mutation in the Kachin region is F446I (19,28).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that although parasite isolates from the two study sites showed widely different in vitro sensitivities to AS and DHA, these values do not correlate with clinical outcomes. Studies conducted along the China-Myanmar border area have shown overall excellent efficacies of ACTs (25)(26)(27), but slowed parasite clearance and 3-day parasite positivity after ACT treatment were also detected (28,29), indicating possible emergence of artemisinin resistance in this region. For the only known molecular marker of artemisinin resistance, pfk13, earlier data showed that the prevalent K13 mutation in the Shan State is P574L (30), which is correlated with artemisinin resistance (8), whereas the most prevalent K13 point mutation in the Kachin region is F446I (19,28).…”
Section: Discussionmentioning
confidence: 99%
“…Several molecular epidemiology studies, mostly in southeast Asia, 27,38,[41][42][43][44] China, [45][46][47][48] Indian subcontinent 49,50 and Africa, 27,51-58 investigated the frequency of K13 mutant alleles, their spatial distribution and, in some cases, their association with clinical artemisinin resistance (day 3 positivity rate or parasite clearance half-life). Only 13 independent K13 mutations of about 100 tested were found to be associated with clinical resistance, with evidence of the independent emergence of the same mutation in different areas.…”
Section: Resistance To Artemisinin Derivatives: Past and Present Resementioning
confidence: 99%
“…The investigators recommended prolonged ART-based combination courses in patients with standard 3-day treatments failures [154] . Several studies were conducted to confirm this link in P. falciparum strains isolated from several Asian countries; Bangladesh [155] , China and Myanmar [156][157][158][159] . On the other hand, its mutation was not prevalent in several African countries; Uganda [151] , Senegal [160] and Mali [161] .…”
Section: Anti-malarial Drugs: P Falciparum Is a Complexmentioning
confidence: 98%